The Constants in A Posteriori Error Indicator for State-Constrained Optimal Control Problems with Spectral Methods - Jianwei Zhou (Abstract and Applied Analysis)
We employ Legendre-Galerkin spectral methods to solve state-constrained optimal control problems. The constraint on the state variable is an integration form. We choose one-dimensional case to illustrate the techniques. Meanwhile, we investigate the explicit formulae of constants within a posteriori error indicator.